2010
DOI: 10.1007/s10606-010-9128-5
|View full text |Cite
|
Sign up to set email alerts
|

Prescriptions, X-rays and Grocery Lists. Designing a Personal Health Record to Support (The Invisible Work Of) Health Information Management in the Household

Abstract: For many years the introduction of Electronic Health Records (EHRs) in medical practice has been considered the best way to provide efficient document sharing among different organizational settings. The actual results of these technologies, though, do not seem to have matched expectations. The issue of document sharing has been lately readdressed by proposing the creation of patient-controlled information and communication technologies, Personal Health Records (PHRs), providing laypeople the tools to access, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…Organizing shared care solutions around individual patients is expected to help overcome existing communication barriers between institutions and across administrative levels. For instance, a shared patient record system, may help to bridge unconnected "islands" and allow a more efficient overall utilization of resources (Ball et al 2007;Piras and Zanutto 2010). Furthermore, providing patients with solutions that will allow them to make informed choices can put them in a quasi-customer role.…”
Section: Drivers For Patient-oriented Ehealth Projectsmentioning
confidence: 99%
“…Organizing shared care solutions around individual patients is expected to help overcome existing communication barriers between institutions and across administrative levels. For instance, a shared patient record system, may help to bridge unconnected "islands" and allow a more efficient overall utilization of resources (Ball et al 2007;Piras and Zanutto 2010). Furthermore, providing patients with solutions that will allow them to make informed choices can put them in a quasi-customer role.…”
Section: Drivers For Patient-oriented Ehealth Projectsmentioning
confidence: 99%
“…Breaking away from the organizing logic of the healthcare system entails first of all making sense of idiosyncratic patient information management practices that remain mostly uncharted. As Piras and Zanutto have pointed out, these practices are in some ways invisible as they are interwoven with everyday routines and objects that are part of the private sphere (Piras and Zanutto 2010). Designing systems adapted to current patient information management practices would require intensive engagement with the everyday Bwork^of patients through an iterative combination of ethnography, (Greenhalgh et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on PHRs' use and user practices has identified a number of tensions. For instance, patients and health providers may have diverging views on personal health information (Piras and Zanutto 2010) and on the distribution of duties among the patient and the provider (Nazi 2013;Turvey et al 2014). Tang and colleagues argue that from a healthcare provider's perspective, not all patient-supplied data can inform providers' decision making; this information could be Bclinically irrelevant^or become overwhelming for a healthcare provider to review (Tang et al 2006).…”
Section: The Phr Conceptmentioning
confidence: 99%
See 2 more Smart Citations